Does bacteriology laboratory automation reduce time to results and increase quality management?. (March 2016) - Dauwalder, O.; Landrieve, L.; Laurent, F.; de Montclos, M.; Vandenesch, F.; Lina, G.
Abstract: Due to reductions in financial and human resources, many microbiological laboratories have merged to build very large clinical microbiology laboratories, which allow the use of fully automated laboratory instruments. For clinical chemistry and haematology, automation has reduced the time to results and improved the management of laboratory quality. The aim of this review was to examine whether fully automated laboratory instruments for microbiology can reduce time to results and impact quality management. This study focused on solutions that are currently available, including the BD Kiestra™ Work Cell Automation and Total Lab Automation and the Copan WASPLab ® .